On the philosophy of diagnosis: is doing more good than harm better than "primum non nocere"?. Issue 4 (23rd March 2009) - Body, R; Foex, B
Abstract : Diagnosis is arguably the cornerstone of medicine. Without at least some form of diagnosis the practice of medicine would not be possible. This narrative review explores common philosophical assumptions and challenges the notion that a certain diagnosis can ever be made. The idealistic concept of "primum non nocere" is discussed, and whether the utilitarian goal of achieving "the greatest happiness for the greatest number" is a feasible or preferable alternative is considered. It is concluded that utilitarianism is inescapably intertwined with modern medical practice. Suggestions are presented to further the understanding of diagnostic medicine by embracing its principles.